2008
DOI: 10.1590/s1413-78522008000500003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da anatomia arterial no pé torto congênito através da ultrassonografia com doppler colorido

Abstract: OBJETIVO: Avaliação ultrassonográfica das artérias tibial anterior e posterior no pé torto congênito (PTC). MATERIAL E MÉTODO: Foram incluídos 20 pacientes portadores de PTC idiopático compreendendo 18 casos unilaterais e dois bilaterais, sendo que 17 pacientes foram submetidos a tratamento cirúrgico e três a tratamento conservador. Todos os pacientes apresentavam pés plantígrados e foram submetidos à avaliação clínica e radiográfica, seguido pelo exame de ultrassom Doppler colorido (UDC), visando a identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…[18] and Pinto et al . [16] used unaffected feet as the control group, and they reported that there was no statistically significant difference in blood flow velocities of affected and unaffected feet. We also detected similar blood flow velocity results for affected and unaffected feet of unilateral clubfoot patients in this study and our previous study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[18] and Pinto et al . [16] used unaffected feet as the control group, and they reported that there was no statistically significant difference in blood flow velocities of affected and unaffected feet. We also detected similar blood flow velocity results for affected and unaffected feet of unilateral clubfoot patients in this study and our previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they suggested a CDU examination to detect arterial deficiency before extensive posterior release. Pinto et al [16]. searched the flow velocities and arterial gauge in a cohort of patients between 5 and 12 years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A incidência para síndrome de Down é de cerca um para cada 660 recém-nascidos e é o padrão de malformação mais comum na população (GIRISHA et al, 2007;ALIO et al, 2008 Pé torto congênito é um termo genérico utilizado para descrever uma afecção congênita complexa do pé, caracterizada por equinismo, cavismo, varismo e adução acentuados, presente isoladamente ou em associação entre 2,17:1.000 e 6,84:1.000 RN (PEREIRA et al, 2008;PINTO et al, 2008). Neste estudo, a forma isolada foi observada em 1,65:1.000 e, quando considerados todos os casos, em 4,6:1.000 RN, valor dentro do esperado.…”
unclassified